2019
DOI: 10.1108/ijesm-07-2019-0005
|View full text |Cite
|
Sign up to set email alerts
|

Natural gas consumption and economic growth nexus: an investigation for France

Abstract: Purpose The purpose of this study is to investigate the relationship between natural gas consumption and economic growth of France. Design/methodology/approach To analyze the relationship, an extended Cobb–Douglas production function is used. The auto-regressive distributive lag bounds testing approach is applied to test the existence of the long-run relationship between the series. The vector error correction model Granger causality approach is implemented to detect the direction of causal relation between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 54 publications
2
10
0
Order By: Relevance
“…The feedback hypothesis considers the bidirectional causal link between economic growth and energy consumption; and the studies of Mutascu (2016) for G7 countries, Saidi et al (2017) for a panel of 53 countries, Bercu et al (2019) for central and eastern European countries support this hypothesis. This hypothesis was also confirmed for some individual country studies like Shahbaz et al (2013) for Indonesia, Islam et al (2013) for Malaysia, and Farhani and Rahman (2019) for France.…”
Section: Economic Growth-energy Use Nexussupporting
confidence: 63%
See 1 more Smart Citation
“…The feedback hypothesis considers the bidirectional causal link between economic growth and energy consumption; and the studies of Mutascu (2016) for G7 countries, Saidi et al (2017) for a panel of 53 countries, Bercu et al (2019) for central and eastern European countries support this hypothesis. This hypothesis was also confirmed for some individual country studies like Shahbaz et al (2013) for Indonesia, Islam et al (2013) for Malaysia, and Farhani and Rahman (2019) for France.…”
Section: Economic Growth-energy Use Nexussupporting
confidence: 63%
“…The subsequent research and empirical evidence identified the direction of causal association between economic growth and energy consumption under four erudite strands for formulating suitable energy policies. These strands are the growth hypothesis, the conservation hypothesis, the feedback hypothesis, and the neutrality hypothesis ( Shahbaz et al., 2013 , 2018 ; Saidi et al., 2017 ; Farhani and Rahman, 2019 ; Bercu et al., 2019 ; Rahman and Velayutham, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Following Farhani and Rahman (2019) , Ozturk et al. (2016) , Rahman (2020b) and Shahbaz et al., 2013a , Shahbaz et al., 2013b , the general empirical model can be expressed as follows: EF = f(TOR, EC, TR, UP) where: EF symbolizes ecological footprints measured in global hectares (gha).…”
Section: Methodsmentioning
confidence: 99%
“…Nadler (2018) shows that electrical rate has an impact on political stability, and Haynes (2016) determined a relationship between the supply of energy and resources, and economic and political stability. Farhani and Rahman (2020) found that there is a causal effect between gas consumption and economic growth in France and between energy and economic growth in Croatia (Vlahinic-Dizdarevic and Zikovic, 2010). In addition, Dey (2019) shows strong evidence of bidirectional causality in Bangladesh between the consumption of electricity and incomes.…”
Section: Energy Market: Economic Growth and Political Stabilitymentioning
confidence: 99%